Teachers and educational policy: Markets, populism, and im/possibilities for resistance - Stacey, Meghan; Gavin, Mihajla; Gerrard, Jessica; Hogan, Anna; Holloway, Jessica (Education Policy Analysis Archives, 2022)
This double special issue, “Teachers and educational policy: markets, populism, and im/possibilities for resistance” explores the figurative politics of the teacher in current education systems around the world. In this introduction to the issue, we discuss how and why teachers have emerged as a key focus of contemporary policy reform. We argue that teachers are seen as a logical site of public commentary in the global knowledge economy, yet teacher expertise is feared as both known and unknowable, thereby becoming a target of heightened surveillance and control. The papers in the issue are divided into two instalments. First, those which address how external actors are seen to be (re)shaping teachers and teaching, as well as notions of professionalism, knowledge and ‘truth’ in education. Second, those which explore experiences of, and possibilities for resistance to, such shifts. We close with a discussion of the range of international contexts from which the contributors to this issue write, arguing for a need to reimagine teachers and schooling in ways that are less limited by the systems and structures that have formed common international reference points in policy development thus far.